Tunable Matched Filter of Light Range - S. A. Baruzdin (Известия высших учебных заведений России: Радиоэлектроника, 2016)
The simulation of the operation of a photonic controller at matched filtering mode is performed. The basis for the simulations are the optical Bloch equations. Using the apparatus of the transition matrices of the system state complex envelopes of two - and three-pulse echo are defined. It is shown that in two-pulse excitation mode the echo corresponds to the pulse characteristic of the fil-ter. In the three-pulse mode stimulated echo corresponds to the output signal of the matched filter. Changing the shape of the excitation signals the filter may be adjustment for it accommodating to signals with various form and parameters.